1969
DOI: 10.1111/j.1151-2916.1969.tb09173.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Graphite‐Uranium Dioxide Reaction from 1400° to 1756°C

Abstract: The reaction of microspheres of UOz with graphite was studied from 1400" to 1756°C. When a spherically symmetrical layer of carbide was produced around the UO, core, only UC, was formed, and the diffusion of oxygen through this layer was rate-controlling. The Arrhenius relation for this system is h,,=21.0 exp( -90,00O/RT) cm'/s The reaction of a geometrically nonsymmetrical configuration of UO, and UC, was also studied. Comparison of the reactions in the symmetrical and nonsymmetrical systems demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1970
1970
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This is a key point in the preparation of the samples, since the reaction between the U x O y and carbon is controlled by the diffusion of carbon and oxygen [28], so that a good contact between the reactants is necessary for the reaction to proceed satisfactorily.…”
Section: Resultsmentioning
confidence: 99%
“…This is a key point in the preparation of the samples, since the reaction between the U x O y and carbon is controlled by the diffusion of carbon and oxygen [28], so that a good contact between the reactants is necessary for the reaction to proceed satisfactorily.…”
Section: Resultsmentioning
confidence: 99%
“…Several have reported difficulty in achieving low oxygen with this technique (Stoops andHamme 1962 andFrost 1963), but more recent work on UC by Matthews and Herbst (1983) showed that with proper care and equipment, the oxygen could be reduced to 360 ±95 ppm. Lindemer et al (1969) reported that removal of oxygen from a spherical UO 2 particle is controlled by diffusion of oxygen through the UC 2 layer of the microsphere to the surface. Suzuki et al (1982) added that the kinetics of the carbothermic synthesis of uranium carbides may be influenced by the characteristics of the UO 2 feed powder and shape of the compacts.…”
Section: Techniques For Fabricating Ug>mentioning
confidence: 99%